Analysis of Legal Protection for Children Victims of Pedophilia Based on Law No. 1 of 2016 Concerning The Second Amendment of Law No. 23 of 2022 Concerning Child Protection - Slamet Pribadi (Ridwan Institute, 2022)
The study belongs to normative law research. The research aims to examine the regulation of paedophilia criminal action in Indonesia that can give law protection to the victim of paedophilia criminal action in Indonesia and to find out the form of an attempt of protection for the victim of paedophilia criminal action. The data employed were secondary data collected using the literary study technique, that is, to collect the secondary data relevant to the problem studied and characterized according to the category. The data collected was then analyzed using a qualitative data analysis method. Based on the research, it can be obtained the legislations that can be used for protecting the victim of paedophilia criminal action in Indonesia include (a) Articles 287 clause (1) of KUHP (Penal Code) and 81 clauses (1) and (2) of Act number 23 of 2002 about Children Protection, governing the criminal act of sexual activity with a child, (b) Articles 289 of KUHP, 290 clauses (2) of KUHP, 290 clauses (3) of KUHP, 292 of KUHP, 293 clauses (1) of KUHP, 294 clauses (1) of KUHP and 82 of Act number 23 of 2002 about the Children protection, governing the criminal acts of sexual abuse to the child, (c) Article 88 of Act number 23 of 2002 about the Children protection, governing the criminal act of child exploitation. Meanwhile, the form of protection the government, nongovernmental agencies and society give to the victim of paedophilia criminal action include counselling, medical service/help, legal assistance, monitoring and prevention.